The New Jobs Tax Credit: An Evaluation of the 1977-78 Wage Subsidy Program - Perloff, Jeffrey M.; Wachter, Michael L. (American Economic Review, 1979)
The New Jobs Tax Credit was one of the four programs in the 1977 economic stimulus package. This program, although viewed primarily as a countercyclical measure, may also alter the equilibrium unemployment rate, UN.' This paper presents our preliminary analysis of the Department of Labor survey, conducted by the Bureau of the Census, in which firms described their responses to this employment tax credit (ETC). To date, our results indicate the potential for a large employment effect. Ordinary least squares estimates suggest that firms which knew about the program increased employment 3 percent faster than other firms. A second analysis which uses multinomial logit techniques indicates that the ETC shifted the entire distribution of employment growth to the right: slowly growing firms increased employment to capture the credit. Since the firms which knew about the program, however, were not randomly drawn, our results may overstate the program's employment effect. Due to the nature of the survey data, we can only focus on direct employment effects.2 It is useful, however, to at least mention the other potential effects of the program. First, unlike Comprehensive Employment Training Act (CETA) programs which increase public employment, the ETC should increase employment in the private sector. Within the private sector, the rules of the current ETC program provide an additional stimulus to the growing industries and, to a lesser extent, to small establishments. Second, the long-run structural effects of this two-year program are probably small. A permanent ETC, however, may be able to lower UN of disadvantaged workers.